Big data analytics : 4th International Conference, BDA 2015, Hyderabad, India, December 15-18, 2015, proceedings /: 4th International Conference, BDA 2015, Hyderabad, India, December 15-18, 2015, proceedings. (2015) - Unknown
No abstract available